Análisis del Impuesto a la Renta del Régimen Microempresas y su Incidencia en la recaudación tributaria en el sector comercial de la ciudad de Loja, períodos 2020 - 2021 - Hidalgo Eras, Maritza del Cisne (2022)
At the international level, all countries need to finance their investments or expenses through tax collection, for this reason they create taxes applied to natural or legal persons; however, the tax burden is assumed by the Micro, small and medium enterprises (Mypimes) since they represent the largest number of taxpayers. Since the application of the Income Tax of the Regime for Micro-enterprises and despite going through the Covid-19 Pandemic, by legal mandate taxpayers whose income ranged from $0.00 to $300,000.00 were registered within an economic group and forced to pay the 2 % of their income, for this reason in this research work the incidence of collection in this sector was analyzed. The study adopted a mixed-methods research approach because it combines and integrates qualitative and quantitative research methods. The methods used were: scientific, deductive, inductive, historical, and comparative; and a survey was applied to 349 participants from a population of 3908 taxpayers. For this research work, it was necessary to analyze the base and the regulatory framework of the Income Tax of the Regime for Micro-enterprises to have a reference of the commercial sector and to know the substantial and formal aspects of this tax. Subsequently, the tax collection for companies in the commercial sector at the national level for the years 2020 and 2021, and the collection by the Tax Regime for Microenterprises (RIM) of the city of Loja were identified and determined. This analysis revealed the perception of the taxpayers who were part of the RIM regime and what they knew about the new Simplified Regime for entrepreneurs and popular businesses (RIMPE), to finally prepare a tax guide that allows taxpayers to adequately fulfill their obligations and formal duties within RIMPE.